Tahfidzul Qur'an Curriculum Media Innovation in Islamic Boarding Schools - Aziz, Mursal; Nasution, Zulkipli; Lubis, M. Syukri Azwar; Suhardi; Harahap, Muhammad Rifai (Tafkir: Interdisciplinary Journal of Islamic Education, 2024)
This research aims to investigate how the curriculum is innovated in the Tahfizhul Qur'an learning media at the Purbabaru Musthafawiyah Islamic Boarding School. The research method used is qualitative. The findings of this research are as follows: The curriculum at the Musthafawiyah Purbabaru Islamic boarding school employs a unique approach, primarily utilizing classical books that are not arranged linearly (Kitab Turash). The Musthafawiyah Islamic Boarding School in Purbabaru, North Sumatra, follows the Mu'ilah curriculum, an internally designed curriculum tailored to the needs of the Islamic boarding school, incorporating various innovations aligned with community needs and the goals established by the school. Among the programs within this curriculum is the Tahfizhul Qur'an program. To support the success of the Tahfizhul Qur'an at the Musthafawiyah Islamic Boarding School in Purbabaru, North Sumatra, appropriate Tahfizhul Qur'an media are necessary. Tahfizhul Qur'an media at the Musthafawiyah Islamic Boarding School in Purbabaru, North Sumatra, facilitate curriculum innovation through the use of specialized Qur'ans, tahfidh tables, blackboards, and Al-Quran murattal. Through the implementation of these media, it is hoped that the curriculum objectives can be achieved successfully, effectively, and efficiently.